DESIGN SONOGRAPHIC PARAMETERS OF LIVER, GALLBLADDER AND PANCREAS IN HEALTHY MEN OF PODILLYA DEPENDING ON THE CHARACTERISTICS OF THE BODY STRUCTURE - Гунас, І.В.; Ковальчук, О.І.; Прокопенко, С.В.; Мельник, М.П. (World of Medicine and Biology, 2016)
Aim of our work – build and conduct analysis of regression models individual normative sonographic parameters of liver, gallbladder and pancreas, according to the characteristics of the structure and size of the body apparently healthy men of Podillya of the first adulthood in general and of different age groups. Materials and methods On the basis of Scientific and Research Center Vinnitsa National Medical University named after Pirogov as a result of a comprehensive survey of urban men by age from 22 to 35, in the third generation residing in Podilskiy region of Ukraine were selected 114 healthy men. Ultrasonography of abdominal organs was performed using ultrasound diagnostic system "CAPASEE" SSA-220A (Toshiba, Japan) convex transducer with an operating frequency of 3.75 MHz according to conventional methods. Defined: slanting vertical size of the right lobe of the liver on inhale and exhale, the thickness of the right lobe of the liver on inhale and exhale, cranio-caudal size and thickness of the left lobe of the liver on inhale and exhale, length and thickness of the caudate lobe of the liver; the diameters of portal vein and the left, right and middle hepatic veins; thickness, width and height of the pancreatic head, thickness and height of the body of the pancreas, thickness and height of the tail of the pancreas; length, width and thickness of the gallbladder, an longitudinal and cross-sectional area of gallbladder. Gallbladder volume calculated by a formula that allows define the volume of ellipse: V=0,524´ length ´ width ´ thickness. Anthropometric survey was conducted in accordance with the scheme V. Bunak in modification of P.P. Shaparenko. To evaluate the somatotype used mathematical scheme of J. L. Carter and B. H. Heath. Component composition of body weight was determined by methods J. Matiegka and the American Institute of Nutrition. To develop normative individual sonographic parameters of liver, gallbladder and pancreas, according to the characteristics of the structure and size of the body men of the first mature age in general and different age groups (under and over 25 years) in license package "STATISTICA 6.1" used method of stepwise regression analysis. Results. Discussions In the total group of men first mature age from 27 possible built only width caudate lobe of the liver model with higher determination coefficient 0,6 (R2 = 0,630); in men from 22 to 25 years built only 3 model (caudate lobe of the liver width, thickness of the head and width of the body of the pancreas, R2 from 0.629 to 0.647); in men from 26 to 35 years built 17 models (7 - 70.0% of the liver size, R2 from 0.669 to 0.816; the diameter of portal and hepatic veins, R2 0,626 and 0.744; length and thickness of the gallbladder, R2 0,687 and 0.724;6 - 85.7% of the pancreas size, R2 from 0.622 to 0.852). When analyzing models built with determination coefficient higher then 0.6, the following percent joining the models groups of anthropo-somatotypological indicators: in men from 22 to 25 years - cephalometric 10.0%, total 0%, 10.0% longitudinal, covering 40,0%, diameters 15.0%, 10.0% WDE, TSFF 10.0%, 0% somatotypological, composition of body weight 0%; in men from 26 to 35 years - cephalometric 17.0%, total 0.9%, longitudinal 10.4%, covering 30.2%, 13.2% diameters, WDE 7.5%, TSFF 16.0%, somatotypological 2.8%, composition of body weight of 1.9%.